Dietary habits in women with recurrent idiopathic calcium nephrolithiasis - Meschi Tiziana; Nouvenne Antonio; Ticinesi Andrea; Prati Beatrice; Guerra Angela; Allegri Franca; Pigna Federica; Soldati Laura; Vezzoli Giuseppe; Gambaro Giovanni; Lauretani Fulvio; Maggio Marcello; et al. (Journal of Translational Medicine, 2012)
Abstract Background Nutrition has been widely recognized to influence the risk of kidney stone formation. Therefore the aim of our study was to assess: a) whether usual diet of women with idiopathic calcium nephrolithiasis (ICN) living in Parma (Northern-Italy) is different compared to healthy controls, b) how their diet differs from Italian National guidelines and c) whether it is related to nephrolithiasis clinical course. Methods 143 women with recurrent ICN (mean age 43 ± 13 ys) and 170 healthy women (mean age 42 ± 11 ys) were enrolled. All women completed a food frequency questionnaire for the last 60-days and a 3-day dietary diary analysed with a dedicated software. Results Stone formers showed a higher consumption of sausages, ham, meat and sweets than healthy controls (43.1% vs 11.1%, 29.4% vs 13.9%, 21.6% vs 4.2%, 66.7% vs 18.1%, p < 0.001). The 3-day diary analysis showed an intake of calories, carbohydrates, lipids and non-discretionary sodium about 10% higher than healthy controls (p < 0.001). Finally, after dividing the population into 3 age groups (≤30, 31-40, > 40 years), the differences described above were amplified in the class ≤30 years, where nephrolithiasis presented a more serious course (shorter recurrence interval, greater stone-rate). In this age group the intake of fruit and vegetables was notably lower than guideline recommendations. Conclusions We conclude that the usual diet of women with recurrent ICN is different from controls and characterized by low intake of fruits and vegetables and higher consumption of simple sugars and foods with high protein and salt content. This dietary imbalance could play a role in the ICN pathogenesis, especially in younger women. This work was financed by grants from Italian Ministry of University and Research as part of a larger project about the prevention of kidney stones (PRIN 2005063822) and by Fondazione per la Ricerca Scientifica Termale (FoRST). No potential conflict of interest relevant to this paper was reported.